SME EMPOWERMENT IN SURABAYA : Case Study Jajan Pasar Association in District Tandes - Berman Surriadi (AdBispreneur : Jurnal Pemikiran dan Penelitian Administrasi Bisnis dan Kewirausahaan, 2016)
ABSTRACT  After the economic crisis hit almost all developing countries in 1997 ago, small and medium enterprises (SMEs) has been demonstrated as a bussiness sector that is able to survive in the storm crisis. The fact is that then able to deflect the direction of governmenteconomic policy. From the pro capitalist becomes more populist. Small and medium enterprisesubsequently deemed to have a strategic role in national economic development. With the flexibility that is owned, SMEs is considered one sector to reduce unemployment and improve people’s lives. The purpose of this research to identify the role of state/government,in case regional government (Pemda Tk II) Kotamadya Surabaya, for empowerment UKM Paguyuban jajan Pasar. How the government’s efforts to give a space conducive to UKM.